How is agitation and restlessness managed in the last 24 h of life in patients whose care is supported by the Liverpool Care Pathway for the Dying Patient?. Issue 3 (1st December 2011) - Gambles, M; McGlinchey, T; Latten, R; Dickman, A; Lowe, D; Ellershaw, J E
Abstract : Background: Guidance regarding the patient centred management of agitation and restlessness reinforces the importance of considering underlying causes, non-pharmacological approaches to treatment and judicious use of medications titrated to patient need. In contrast, recent reports in the literature suggest that the practice of continuous deep sedation until death is prevalent in the UK. Aim: To use data from the National Care of the Dying Audit - Hospitals (NCDAH) to explore the administration of medication for management of agitation and restlessness in the last 24 h of life. Methods: Hospitals submitted data from up to 30 consecutive adult patients whose care in the final hours/days of life was supported by the Liverpool Care Pathway for the Dying Patient (LCP). Data on the total dose received in the last 24 h of life PRN and the last dose prescribed for administration via continuous subcutaneous infusion (CSCI) for agitation and restlessness were submitted. Results: 155 hospitals provided data from 3893 patients. Median total doses in the last 24 h for midazolam, haloperidol and levomepromazine, respectively, were: PRN only, 2.5, 1.5 and 6.25 mg; CSCI only, 10, 3 and 6.25 mg; PRN+CSCI, 15, 3 and 12.5 mg. Conclusion: Only 51% of patients received medication to alleviate agitation and restlessness in the last 24 h of life. Median doses were low in comparison to doses recommended for continuous deep sedation, suggesting that there is no 'blanket' policy for continuous deep sedation at the end of life for patients whose care is supported by the LCP.